2020
DOI: 10.3803/enm.2020.35.2.260
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on Vascular Complications in Patients with Type 2 Diabetes Mellitus

Abstract: It is well known that patients with type 2 diabetes mellitus (T2DM) are at an increased risk of morbidity and mortality from atherosclerotic cardiovascular (CV) complications. Previously, the concept that diabetes mellitus (DM) is a "coronary artery disease (CAD) risk equivalent" was widely accepted, implying that all DM patients should receive intensive management. However, considerable evidence exist for wide heterogeneity in the risk of CV events among T2DM patients and the concept of a "CAD risk equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Microalbuminuria is a marker of cardiovascular disease risk and should be monitored per guidelines once or twice a year for progression to macroalbuminuria and kidney disease development, especially if plasma glucose, lipids and blood pressure are at guideline goals. microalbuminuria can be used as an independent marker for early prediction of cardiovascular complications and can be used as a screening procedure in all patients diagnosed with T2DM [18,21]. Determining a patient's ACR will provide an overview of other complications besides DN that can developed in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Microalbuminuria is a marker of cardiovascular disease risk and should be monitored per guidelines once or twice a year for progression to macroalbuminuria and kidney disease development, especially if plasma glucose, lipids and blood pressure are at guideline goals. microalbuminuria can be used as an independent marker for early prediction of cardiovascular complications and can be used as a screening procedure in all patients diagnosed with T2DM [18,21]. Determining a patient's ACR will provide an overview of other complications besides DN that can developed in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…DM is classified into type 1 DM (T1DM), resulting from autoimmune-induced β -cell death; type 2 DM (T2DM), due to insulin resistance or impaired insulin secretion (that accounts for >90% of diagnosed DM cases); gestational DM; and specific types of DM due to other causes, e.g., chemical-induced diabetes [ 97 ]. Hyperglycemia can affect both the macro- and microvasculature leading to end-organ damage that is responsible for the morbidity and mortality seen in DM [ 98 100 ].…”
Section: Study Of Ecfcs To Help Decipher Disease Pathogenesismentioning
confidence: 99%
“…Atherosclerotic cardiovascular disease (ASCVD) is a common complication and a leading cause of death in patients with type 2 diabetes mellitus (T2DM) [ 1 ]. Studies have confirmed that ASCVD can be prevented by controlling cardiovascular risk factors in patients with T2DM [ 2 ].…”
Section: Introductionmentioning
confidence: 99%